Ectopic Expression of JcWRKY Transcription Factor Confers Salinity Tolerance via Salicylic Acid Signaling - Agarwal, Parinita; Dabi, Mitali; Sapara, Komal K.; Joshi, Priyanka S.; Agarwal, Pradeep K. (Frontiers in Plant Science, 2016)
Plants, being sessile, have developed intricate signalling network to specifically respond to the diverse environmental stress. The crop performance and yield is limited due to exposure of multiple stresses simultaneously. The coordinated crosstalk between different signalling components, including phytohormones and transcription factor(s) play a crucial role towards increased stress resistance in crops. Transcription factors play an important role in regulating the downstream processes during stress. The plant-specific WRKY TFs form one of the largest TF family and are involved in diverse plant processes, involving growth, development and stress signalling through auto and cross regulation with different genes and TFs. The salicylic acid -inducible JcWRKY TF confers salinity tolerance in transgenic tobacco, as was evident by increased chlorophyll content and seed germination potential. The transgenic plants showed increased soluble sugar, membrane stability, reduced electrolyte leakage and generation of reactive oxygen species (H2O2 and O2•−) as compared to the wild type (WT). Furthermore, the low SA treatment along with salinity improved the tolerance potential of the transgenics by maintaining ROS homeostasis and high K+/Na+ ratio. The transcript expression of SA biosynthetic gene ICS1 and antioxidative enzymes (CAT and SOD) showed upregulation during stress. Thus, the present study reflects that JcWRKY might be working in co-ordination with SA and salt stress signalling to orchestrate the different biochemical and molecular pathways to manoeuvre stress tolerance of the transgenic plants.